EFFECT OF GENISTEIN AND OROBOL ISOFLAVONES ON FE2+/ ASCORBATE INDUCED LIPID PEROXIDATION IN LIVER AND HEART MITOCHONDRIA OF RATS AND CENTRAL ASIAN STEPPE TURTLES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article studied the effect of genistein and orobol isoflavones on Fe2+/ascorbate-induced LPO (lipid peroxidation) in mitochondria of the liver and heart of the Central Asian steppe turtle rat. In particular, it was studied the inhibitory effect of genistein and orobol on the swelling of liver and heart mitochondria in warm-blooded and cold-blooded animals with the help of Ca2+ ions. In addition, their inhibitory effect on Fe2+/ascorbate-induced LPO and a decrease in the content of MDA (malonic dialdehyde) in mitochondrial membranes of rat liver and Central Asian steppe turtle were studied.